Review on dog rabies vaccination coverage in Africa: a question of dog accessibility or cost recovery? - Tariku Jibat; Henk Hogeveen; Monique C M Mourits (PLoS Neglected Tropical Diseases, 2015)
BACKGROUND:Rabies still poses a significant human health problem throughout most of Africa, where the majority of the human cases results from dog bites. Mass dog vaccination is considered to be the most effective method to prevent rabies in humans. Our objective was to systematically review research articles on dog rabies parenteral vaccination coverage in Africa in relation to dog accessibility and vaccination cost recovery arrangement (i.e.free of charge or owner charged). METHODOLOGY/PRINCIPAL FINDINGS:A systematic literature search was made in the databases of CAB abstracts (EBSCOhost and OvidSP), Scopus, Web of Science, PubMed, Medline (EBSCOhost and OvidSP) and AJOL (African Journal Online) for peer reviewed articles on 1) rabies control, 2) dog rabies vaccination coverage and 3) dog demography in Africa. Identified articles were subsequently screened and selected using predefined selection criteria like year of publication (viz. ≥ 1990), type of study (cross sectional), objective(s) of the study (i.e. vaccination coverage rates, dog demographics and financial arrangements of vaccination costs), language of publication (English) and geographical focus (Africa). The selection process resulted in sixteen peer reviewed articles which were used to review dog demography and dog ownership status, and dog rabies vaccination coverage throughout Africa. The main review findings indicate that 1) the majority (up to 98.1%) of dogs in African countries are owned (and as such accessible), 2) puppies younger than 3 months of age constitute a considerable proportion (up to 30%) of the dog population and 3) male dogs are dominating in numbers (up to 3.6 times the female dog population). Dog rabies parenteral vaccination coverage was compared between "free of charge" and "owner charged" vaccination schemes by the technique of Meta-analysis. Results indicate that the rabies vaccination coverage following a free of charge vaccination scheme (68%) is closer to the World Health Organization recommended coverage rate (70%) than the achieved coverage rate in owner-charged dog rabies vaccination schemes (18%). CONCLUSIONS/SIGNIFICANCE:Most dogs in Africa are owned and accessible for parenteral vaccination against rabies if the campaign is performed "free of charge".